HUBUNGAN ANTARA FREKUENSI MENYIKAT GIGI DENGANSTATUS DMF-T PADA ANAK USIA 10-12 TAHUN DISDN KEDUNGMALING KECAMATAN SOOKOKABUPATEN MOJOKERTO - Nur So?emah, Eka; Suharni, Elis (JURNAL KEPERAWATAN SEHAT, 2015)
The first problem of dental and oral disase in Indonesia is carier which its increase in each decade. Caries prevention is done by brushing. For technique of WHO health status, determining dental gives a score or value to affect dental caries what dental is repaired (D=Decay), teeth are taken due to caries (M=Missing) and teeth are repaired (F=Filled), and T (Teeth/Total). The purpose of this research investigated the relationship between frequency of tooth brushing with DMF-T to children who were aged 10-12 years old in SDN Kedung Maling Sooko Mojokerto. The research’s method was analytical observational cross-sectional approach and the population was 145 children. The reseach’s sampling used stratified propotional random sampling. Independent variable was frequenty of tooth brushing and dependent variable was status DMF-T. Data was collected by means of interviewing and it was done by observation to 145 children. Data was processed by spearman rho test whit SPSS 16.0. The result showed r value (0.667) >a (0.05), so that Howas accepted, the meaning was no correlation between frequency of thoot brushing with DMF-T status. Many factors what causdental caries, one of them is not exactly when the children brush their teeth such as the method, duration, thoot paste, and great time as well containing diet is carbohydrate and glucose. The children who consum food more that it is contain carbohydrate and glucose, rarely they clean their teeth after eating, they will get dental caries problem. So incidence of dental caries is increase.Keywords: Thoot brushing, DMF-T status, Caries